Integrating Functional Conjunction Instruction within Bilingual Children’s Story Texts: Effects of the Index Card Match Learning Model - Ridwan, M.; Firmansyah, Mochamad Bayu (Universitas Muhammadiyah Malang, 2025)
The ability to understand functional conjunctions is essential in building a cohesive and coherent discourse, but this aspect is still underappreciated in bilingual learning in elementary schools. Many students have difficulty contextualizing conjunctions because learning focuses on grammatical forms rather than functions in authentic texts. This study aims to test the effectiveness of integrating functional conjunction instruction from bilingual texts into the Index Card Match learning model in improving students' grammatical comprehension. The research design used was a quasi-experiment with a pretest-posttest non-equivalent control group approach, involving 60 students in class V who were randomly divided into experimental and control groups. The experimental group received conjunction learning through bilingual text-based Index Card Match activities, while the control group used conventional methods. Data was collected through a multiple-choice test of 30 questions and then analyzed using validity, reliability, normality, homogeneity, ANOVA, and t-test. The results showed a significant increase in post-test scores in the experimental group (M = 82.43; SD = 6.12) compared to the control group (M = 74.10; SD = 7.55) with p < 0.001. These findings show that integrating functional linguistic features through interactive and collaborative strategies effectively strengthens students' conceptual understanding. The novelty of this study lies in the explicit incorporation of micro-elements of discourse into cooperative learning models, which have not been widely applied in grammatical learning in bilingual contexts. The practical implications support the development of contextual, inclusive, and discourse-oriented grammar teaching strategies in multilingual classrooms.